Synthesis of fluorescent alanines by a rhodium catalysed conjugate addition of arylboronic acids to dehydroalanine derivatives - Ferreira, Paula M. T. (2013)
Several arylalanine derivatives containing fluorescent groups were prepared in good yields using a rhodium catalysed conjugate addition of arylboronic acids to N,N-diprotected and N-monoprotected dehydroalanines. The best conditions for these reactions require the use of an excess of aryl boronic acid (4 equiv.), [Rh(COD)2]BF4 as catalyst and CsF as base in dioxane:H2O (10:1) at 110 ºC. These conditions were also applied to several dipeptides with dehydroalanine residues. The photophysical properties of some of the arylalanines were studied in three solvents of different polarity. Due to the absence of the, double bond, the absorption and fluorescence emission of the new compounds are dominated by the photophysical properties of the polycyclic aromatic fluorophores (naphthalene, phenanthrene and pyrene). Considering the relatively high fluorescence quantum yield of these compounds, some of them may be useful as fluorescent markers for peptides and proteins.